If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y = 45 + -3y Solving 6y = 45 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 6y + 3y = 45 + -3y + 3y Combine like terms: 6y + 3y = 9y 9y = 45 + -3y + 3y Combine like terms: -3y + 3y = 0 9y = 45 + 0 9y = 45 Divide each side by '9'. y = 5 Simplifying y = 5
| 7+(-1)+12-7=x | | (-11)-(-14)+7=x | | 9+6(2)7n= | | 0.5x-1.4=1.1 | | (-7)-(-2)-9=x | | -6-1=-32y+32 | | 16-(-13)-(-5)=x | | 6(y-4)=5[17-3(2y-13)] | | 4-5+7k=33 | | -9-200x+(0.015)(100)= | | (-16)-6+(-5)=x | | 12+0.4(x-2)=10 | | 6(x+2)+4=-6 | | 52x=104 | | 8y-5=6y+7 | | -33m-14=85 | | 5x+5x+3+8=5x+4+4x | | -r+259=-124 | | -2x^2+12x+3=0 | | 3(3+2r)=5-6(r+2) | | 3(2x-4)=5(x+6) | | 7x-6-4x=4x-3 | | 2.1x+1=7 | | 9x-3x=-26+2 | | 7-7x=29x+21 | | 17X^43=100000 | | 145-13= | | 6x+4-4=20 | | 2(w+6)+4=2w+16 | | 75+13w=335 | | 9m=3(8m+30) | | 10+2x-x^2=0 |